Dissolved major and trace geochemical dynamics in Antarctic lacustrine systems - Lecomte, Karina L; Vignoni, Paula A; Echegoyen, Cecilia V; Santolaya, Pia; Kopalová, Kateřina; Kohler, Tyler J; Roman, Matěj; Coria, Silvia H; Lirio, Juan M (Chemosphere, 2020)
Clearwater Mesa (James Ross Island, northeast Antarctic Peninsula) provides a unique opportunity to study solute dynamics and geochemical weathering in the pristine lacustrine systems of a high latitude environment. In order to determine major controls on the solute composition of these habitats, a geochemical survey was conducted on 35 lakes. Differences between lakes were observed based on measured physico-chemical parameters, revealing neutral to alkaline waters with total dissolved solids (TDS) < 2500 mg L-1. Katerina and Trinidad-Tatana systems showed an increase in their respective TDS, total organic carbon values, and finner sediments from external to internal lakes, indicating an accumulation of solutes due to weathering. Norma and Florencia systems exhibited the most diluted and circumneutral waters, likely from the influence of glacier and snow melt. Finally, isolated lakes presented large variability in TDS values, indicating weathering and meltwater contributions at different proportions. Trace metal abundances revealed a volcanic mineral weathering source, except for Pb and Zn, which could potentially indicate atmospheric inputs. Geochemical modelling was also conducted on a subset of connected lakes to gain greater insight into processes determining solute composition, resulting in the weathering of salts, carbonates and silicates with the corresponding generation of clays. We found CO2 consumption accounted for 20-30% of the total species involved in weathering reactions. These observations allow insights into naturally occurring geochemical processes in a pristine environment, while also providing baseline data for future research assessing the impacts of anthropogenic pollution and the effects of climate change.
Keywords: Organic Chemicals; uhličitany; Weather; geologické sedimenty; Climate Change; Ice Cover; olovo; stopové prvky; klimatické změny; jezera; monitorování životního prostředí; Trace Elements; Zinc; Carbonates; Minerals; Lead; zinek; Trinidad and Tobago; Antarktida; počasí; Antarctic Regions; Environmental Monitoring; ledový příkrov; minerály; Trinidad a Tobago; ekosystém; organické látky; Geologic Sediments; Ecosystem; Lakes